New taxa of Elimaeini (Orthoptera: Tettigoniidae: Phaneropterinae) from South East Asia - Ingrisch, Sigfrid (Zootaxa, 2011)
Based on specimens in various museum collections one new subgenus and six new species of Elimaeini are described: Poaefoliana subgen. n. (type species Locusta poaefolia De Haan, 1842) of Elimaea Stål, 1874; Elimaea (Poaefoliana) albimaculata sp. n., E. (P.) jitra sp. n., E. (P.) kutu sp. n., Elimaea (Schizelimaea) singgalang sp. n., Orthelimaea kanburi sp. n., O. volsella sp. n. Three classical species were also combined with the new subgenus: Elimaea (Poaefoliana) poaefolia (De Haan, 1842) comb. n., E. (P.) rosea Brunner v. Wattenwyl, 1878 comb. n., E. (P.) jacobsoni Karny, 1926 comb. n. A lectotype for E. rosea is fixed as the type series is not homogenous.